2014
DOI: 10.1021/nn405663h
|View full text |Cite
|
Sign up to set email alerts
|

The Surprising in Vivo Instability of Near-IR-Absorbing Hollow Au–Ag Nanoshells

Abstract: Photothermal ablation based on resonant illumination of near-infrared-absorbing noble metal nanoparticles that have accumulated in tumors is a highly promising cancer therapy, currently in multiple clinical trials. A crucial aspect of this therapy is the nanoparticle size for optimal tumor uptake. A class of nanoparticles known as hollow Au (or Au–Ag) nanoshells (HGNS) is appealing because near-IR resonances are achievable in this system with diameters less than 100 nm. However, in this study, we report a surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
143
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(151 citation statements)
references
References 59 publications
7
143
0
1
Order By: Relevance
“…[25,26] After adding HAuCl 4 into the CTAB-Ag NR dispersion, the combined galvanic reaction (See the Reaction 1) and Kirkendall growth lead to the formation the Au NTs with hollow interiors and porous walls. [27,28] 3Ag (s) + AuCl 4 -(aq) → Au(s) + 3Ag that is, the ends of this NT are terminated by {111} facets, and the side surfaces are bounded by {100} facets, [29][30][31] providing further support for the above-mentioned morphological features observed from the real space TEM images of the Au NTs ( Figure 2B and D) and the diffraction patterns from X-ray diffraction (XRD) ( Figure S4). Further structural information of the Au NTs, (e.g.…”
Section: Synthesis and Length Control Of Gold Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…[25,26] After adding HAuCl 4 into the CTAB-Ag NR dispersion, the combined galvanic reaction (See the Reaction 1) and Kirkendall growth lead to the formation the Au NTs with hollow interiors and porous walls. [27,28] 3Ag (s) + AuCl 4 -(aq) → Au(s) + 3Ag that is, the ends of this NT are terminated by {111} facets, and the side surfaces are bounded by {100} facets, [29][30][31] providing further support for the above-mentioned morphological features observed from the real space TEM images of the Au NTs ( Figure 2B and D) and the diffraction patterns from X-ray diffraction (XRD) ( Figure S4). Further structural information of the Au NTs, (e.g.…”
Section: Synthesis and Length Control Of Gold Nanotubesmentioning
confidence: 99%
“…[37] Furthermore, the reduced Ag content implies more Ag has been etched from the NTs, increasing the porosity and surface defects (as shown in Figure S7), which may also contribute to the observed redshift. [28,33,[38][39][40] …”
Section: Tunable Nir Absorbance Of the Gold Nanotubesmentioning
confidence: 99%
“…However, this concrete step toward the improved clearance brings new questions such as the stability of the nanoparticle assembly and controllability of the biodegradation process. In another recent study, Goodman et al reported the instability of hollow Au-Ag nanoshells, which provide shell structures with dimensions smaller than 100 nm, during in-vivo applications [38]. Another approach to red-shift the plasmonic resonance is to engineer the nanoparticle aspect ratio.…”
mentioning
confidence: 99%
“…The broader resonance peak obtained from TiN nanoparticles is another advantage that relaxes the restrictions on particle size dispersion. It should be noted that smaller nanoparticle dimensions are desirable due to many critical requirements including efficient cellular uptake and clearance of particles after treatment [1,37,38].…”
mentioning
confidence: 99%
“…Conversely, nanoparticle size and geometry can be adjusted to maintain a constant plasmon resonance frequency in some plasmonic nanoparticles over a relatively large particle size range. (1) While much attention has been paid to the tuning of plasmon resonance energies, far fewer studies have examined mechanisms for controlling nanoparticle plasmon line widths and line shapes. For the dipolar plasmon mode of a metallic nanosphere, the line width changes with increasing nanoparticle size, a characteristic signature of a bright plasmon mode.…”
Section: Introductionmentioning
confidence: 99%